If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4n + 18 = -3n + -5 Reorder the terms: 18 + -4n = -3n + -5 Reorder the terms: 18 + -4n = -5 + -3n Solving 18 + -4n = -5 + -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. 18 + -4n + 3n = -5 + -3n + 3n Combine like terms: -4n + 3n = -1n 18 + -1n = -5 + -3n + 3n Combine like terms: -3n + 3n = 0 18 + -1n = -5 + 0 18 + -1n = -5 Add '-18' to each side of the equation. 18 + -18 + -1n = -5 + -18 Combine like terms: 18 + -18 = 0 0 + -1n = -5 + -18 -1n = -5 + -18 Combine like terms: -5 + -18 = -23 -1n = -23 Divide each side by '-1'. n = 23 Simplifying n = 23
| 2n/8=2/5 | | -6-2+8=-11-5p | | 6x-10+2x+8= | | 2p/8-20=-30 | | K^2+12k-16=-3 | | 5*x-8*x=60 | | (-8z+4)+(7z-7)= | | 8x-(2x-3)=3(x-4) | | 0.75-1/2(1/2-3) | | -4(p+9)=24.8 | | 7x-44=13+4x | | 2x-4+x+8=180 | | 6(x-5)=66/11 | | 11y*y= | | 6(6-5)=66/11 | | x+16=4x-7 | | 31=-.06m | | 29b^2+48-88b=0 | | Log[5](x-3)-log[5](x+4)=2 | | (6+3d)-3d=-10 | | 13(7x-8)=9x-6 | | 17x+48=180 | | -7(7x+5)-5= | | 31=-.06 | | 6(2v)= | | 3(4/9)-5y=1 | | (2/3)z=4(1/4) | | g(6)=-2x+4 | | 15x^2-12x-99=0 | | 11v+8=9v-18 | | 3a+4b=7b-a | | 17x+48=90 |